2003
DOI: 10.14411/fp.2003.033
|View full text |Cite
|
Sign up to set email alerts
|

Myxozoans infecting the sharptooth catfish, Clarias gariepinus in the Okavango River and Delta, Botswana, including descriptions of two new species, Henneguya samochimensis sp. n. and Myxobolus gariepinus sp. n.

Abstract: Abstract. During a recent investigation of parasites infecting fishes from the Okavango River and Delta, Botswana (southern Africa) fourteen sharptooth catfish, Clarias gariepinus (Burchell, 1822) (Siluriformes: Clariidae) were examined for the presence of myxozoan infections. Results revealed the presence of two species of the genus Henneguya Thélohan, 1895 and one species of the genus Myxobolus Bütschli, 1882 infecting this fish host. Two of the sampled fish exhibited large plasmodia of Henneguya suprabranch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…The prevalence of 19.79 % in this study is rather similar to the level infection of 18.3 % found for Myxobolus dahomeyensis in the ovaries of Sarotherodon melanotheron melanotheron (Gbankoto et al 2001a) and 21 % of Myxobolus gariepinus found in Clarias gariepinus (Reed et al 2003). Gbankoto et al (2001a) also recorded an infection rate of 31.6 % in the ovaries of Tilapia zillii for M. dahomeyensis while Mansour et al (2013) reported 55.5 % of Kudoa azevedoi from oocytes of Trachurus trachurus.…”
Section: Infection Rate and Spore Descriptionsupporting
confidence: 87%
See 1 more Smart Citation
“…The prevalence of 19.79 % in this study is rather similar to the level infection of 18.3 % found for Myxobolus dahomeyensis in the ovaries of Sarotherodon melanotheron melanotheron (Gbankoto et al 2001a) and 21 % of Myxobolus gariepinus found in Clarias gariepinus (Reed et al 2003). Gbankoto et al (2001a) also recorded an infection rate of 31.6 % in the ovaries of Tilapia zillii for M. dahomeyensis while Mansour et al (2013) reported 55.5 % of Kudoa azevedoi from oocytes of Trachurus trachurus.…”
Section: Infection Rate and Spore Descriptionsupporting
confidence: 87%
“…Furthermore, natural populations of C. gariepinus form a staple diet for many subsistence farmers throughout the African continent. Coinciding with the growing economic value of this fish is the increased interest in its parasite loads and what effect they might hold for the aquaculture industry (Reed et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of morphological and dimensional comparison of the spores, several species of Henneguya are found to resemble the present form (Table 2): Henneguya clariae Abolarin (1971) infecting the gills of C. gariepinus in Nigeria; Henneguya shaharini Shariff (1982) infecting the gills of the marble goby, Oxyeleotris marmoratus in Malaysia; Henneguya bopeleti Fomena and Bouix (1987) infecting the gills of the catfish Chrysichthys nigrodigitatus in Cameroon; H. suprabranchiae Landsberg (1987) infecting the suprabranchial organs of C. gariepinus in Israel; H. branchialis Ashmawy et al (1989) infecting the suprabranchial organ of C. gariepinus in Egypt; Henneguya nyongensis Fomena and Bouix (1996) infecting the gills and muscles of Marcusenius moorii in Cameroon; and H. samochimensis Reed et al (2003) infecting the suprabranchial organ of C. gariepinus in Botswana.…”
Section: Discussionmentioning
confidence: 99%
“…Then, Ashmawy et al (1989) described another species, Henneguya branchialis from the same site and the same fish host collected from Egypt. Later on, Reed et al (2003) described Henneguya samochimensis from the same site and the same fish host collected from Botswana. The histological impacts of H. suprabranchiae and H. samochimensis on the suprabranchial organs were described by El-Mansy and Bashtar (2002) and Reed et al (2003), respectively.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation